IMPROVING THE STUDENTS’ READING COMPREHENSION BY USING PQ4R STRATEGY TO THE EIGHTH GRADE AT SMP NEGERI 2 PANCUR BATU - Br Rajagukguk, Sartika Margaret; Tarigan, Karisma E.; Ginting, Fiber Yun A. (Kairos English Language Teaching Journal, 2020)
Reading is one of the four language skills in English, they are listening, speaking, reading and writing. The students get bored in reading comprehension. Since they do not understand the text. Thus, they need some ways or strategy which could help students’s reading comprehension on narrative text. The teacher should be creative to search for interesting strategy to teach reading comprehension on narrative text. PQ4R strategy can helps the students to understand on narrative text. The objectives of this study to find out the students’ reading comprehension bu using PQ4R strategy. The subject of this study were the eight grade students of SMP 2 Negeri Pancur Batu. This research, the writer used Classroom Action Research (CAR) as the method of research. Tests were used to gather the quantitative data. Based on the finding of this study, it showed in pre-test only 4 students (11%) who passed KKM ( the Mastery Minimum Criteria), and post test 25 students (71%). The result of this research revealed that there was a significant improvement of the students’ achievement from the pre-test to in the post test. This improvement was shown by the comparison between the mean score of pre-test (51,2), and post test (73,82). Furthermore, the students were interested in PQ4R strategy, it can be seen from the result of observation sheet and questionnaire .Therefore, PQ4R startegy was effective strategy in helping students to improve their reading comprehension especially in narrative text.